Implementation of the Tadabur Alam Learning Approach in Increasing Santri Faith at TPQ Nurud Dzolam, Sukasari Village, Pulosari District, Pandeglang Regency, Banten - Naylur Rosyid; Eha Suhayati (al-Afkar, Journal For Islamic Studies, 2025)
This research discusses the benefits of the natural tadabur learning approach in increasing the faith of students at the Nurud Dzolam Al-Qur'an Education Park (TPQ). The natural tadabur learning approach is an activity of contemplating the greatness of Allah through the signs in the universe. This activity is routinely carried out at TPQ Nurud Dzolam to strengthen students' belief in the creation of Allah. This research uses a qualitative method with a case study approach, involving students, ustadz/ustadzah, and TPQ managers as subjects. The research results show that the natural tadabur learning approach has a positive impact in increasing students' faith through direct spiritual experience, awareness of the greatness of Allah, and the formation of tawadhu' character. Supporting factors for implementing this activity include full support from TPQ managers, student enthusiasm, and a supportive natural environment. However, obstacles such as erratic weather conditions and resource constraints affect the consistent implementation of activities. This research recommends improving facilities, developing learning modules for the natural learning approach, as well as integrating this activity with the academic curriculum to maximize its benefits.